Study on the use of SSR markers linked to rust resistance for identification of F3 inbreed groundnut lines obtained by a cross between ICG950166 and L12 cultivars - Phòng Đinh Thị; Thủy Chu Thị; Thắng Bùi Văn; Thắng Nguyễn Văn; Yến Nguyễn Thị; Bình Lê Trần; Muội Lê Thị (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 89-98, 2005